A Collaborative Optimization Model for Ground Taxi Based on Aircraft Priority. (20th November 2013) - Jiang, Yu; Liao, Zhihua; Zhang, Honghai
Abstract : Large hub airports have gradually become the "bottleneck" of the air transport network. To alleviate the "bottleneck" effect, optimizing the taxi scheduling is one of the solutions. This paper establishes a scheduling optimization model by introducing priority of aircraft under collaborative decision-making mechanism, and a genetic algorithm is designed to verify the scheduling model by simulating. Optimization results show that the reliability of the model and the adjusted genetic algorithm have a high efficiency. The taxiing time decreases by 2.26% when compared with an empirical method and the flights with higher priorities are assigned better taxi routes. It has great significance in reducing flight delays and cost of operation.